Electrical Tracking Formation on Silane Epoxy Resin under Various Contaminants - Abdul Syakur; Hamzah Berahim; Tumiran Tumiran; Rochmadi Rochmadi (Universitas Ahmad Dahlan, 2013)
Contamination at the surface of the insulator becomes a serious problem. Especially for the tropical area, humidity and rainfall play an important role in wetness by the water at the insulator surface, which result in the presence of contaminant and leakage current flowing at the surface. This leakage current will generate heat which occurs at the surface of an insulator. This ultimately leads to flashover. This paper presents the influence of contaminants to leakage current and formation of electrical tracking at the surface of epoxy resin compound wit silicon rubber. The test was based on IPT method with NH4Cl as contaminants. The industrial and coastal contaminants are used to explain the effect of contaminant at surface tracking process. The flow rate of contaminant was 0.3 ml/min. The 3.5 kV AC high voltage 50 Hz was applied to the top electrodes. It is found that industrial contamination resulting in the smallest surface leakage current is 327.6 mA. Also it is found that coastal contaminant showed the severest damage at surface of test sample. Therefore, special treatment of the sample is needed under these conditions so that the material performance can be improved, especially against the electrical tracking.